Recovery of motor imagery ability in the first year after stroke. Issue 2 (June 2016) - Feenstra, Wya; Tepper, Marga; Boonstra, Anne M.; Otten, Bert; de Vries, Sjoerd
Abstract : The aim of this study was to examine the level and recovery of motor imagery ability (MIA) in the first year after stroke and whether the recovery of MIA is related to that of arm/hand function. Twenty-three patients with diminished arm/hand function were included. The accuracy score on the hand laterality judgment task was used to assess MIA and the Fugl-Meyer Assessment was used to evaluate the recovery of arm/hand function. The patients were assessed 3, 6, 16, 26, and 52 weeks after stroke. In the first year after stroke, the percentage of patients with moderate to good MIA improved from 78% after 3 weeks to 94% after 1 year. The recovery of MIA took place in the first 6 weeks after stroke. No correlation was found between the recovery of MIA and arm/hand function, despite the fact that the greatest improvement in both occurred in the first 6 weeks.